A política criminal e os efeitos de uma nova regulamentação das drogas no Brasil - Chaim, Fabio Fernandes (2015)
The present study has as main theme the Brazilian anti-drugs policy while a historic process focused on public health protection, whose evolution resulted in a particular criminal approach, the so-called prohibition model endowed of a disproportionate cost-benefit ratio. The law 11.343/06 is resulted from this historic evolution process possessing mechanisms which allow criminalization, imprisonment expansion and detach their interpretation from criminal principles, as well as rights and constitutional guarantees established in the Federal Constitution. In the final decades of the XX century several countries adopted new alternative models of public policy for the theme, which in conjunction with the existing regulation in Brazil for substances like alcohol, tobacco and medicines demonstrate the feasibility of juridical alternatives to criminal oversight job. Indeed, a new regulation of low risk substances acts over the prohibition costs, protecting users health, controlling consumption, reducing power of big criminal organizations and influencing the Public Power role on the sense of satisfaction with Social and Democratic state by rule of law